33.6k views
0 votes
Rewrite a. an = 19 - 7(n-1)

User Vural
by
5.2k points

1 Answer

3 votes

Solution for an=19-7(n-1) equation:

Simplifying

an = 19 + -7(n + -1)

Reorder the terms:

an = 19 + -7(-1 + n)

an = 19 + (-1 * -7 + n * -7)

an = 19 + (7 + -7n)

Combine like terms: 19 + 7 = 26

an = 26 + -7n

Solving

an = 26 + -7n

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Divide each side by 'n'.

a = 26n-1 + -7

Simplifying

a = 26n-1 + -7

Reorder the terms:

a = -7 + 26n-1

User Ivan Prodanov
by
4.6k points